Self-combustion Synthesis of Ni Catalysts Modified with La and Ce using Glycine–Nitrate Process (GNP) - Mohamad Muzakkir, Tajuddin; Muhammad Hasbullah, Patulla; Asmida, Ideris; Mazni, Ismail (Dept. of Chemistry, UTM, 2017)
Combustion synthesis has become an attractive method for preparing oxides and metallic materials for various applications including catalysts. One common combustion route is glycine–nitrate process (GNP). GNP involves a self-sustained reaction between metal nitrates (oxidizer) and glycine (fuel). The process is known to be rapid and simple, and generates catalyst powders that are high purity, crystalline and homogenous. In this work, Ni catalysts modified with La and Ce were synthesized using GNP. A precursor solution containing a stoichiometric mixture of metal nitrates was initially mixed with glycine at various glycine-nitrate ratios (G/N=0.5, 1.0, 1.5). The glycinenitrate solution was then heated to yield a gel-like liquid. The gel was further heated until it self-ignited and produced an ash powder. The catalyst ash was calcined at different temperatures (600‒800°C) and then reduced at 700°C. Catalyst characterization was performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Once produced using GNP, the La element in Ni catalyst modified with La was presence in a form of LaNiO phase. After reduction, Ni catalyst modified with La contains only Ni and La2O3 phases. Meanwhile, Ce element in the Ni catalyst modified with Ce presence as CeO2 phase after the GNP combustion. The CeO2 phase remains after the reduction process and the reduced Ni catalyst modified with Ce composed of two separated phases; Ni and CeO2. Glycine-nitrate (G/N) ratio shows a significant effect on the morphology of the catalysts. At G/N=0.5, where the fuel composition is less than the stoichiometric ratio, the ‘cottonwool-like’ and highly porous structure were observed for both Ni catalysts modified La and Ce. At the fuel composition higher than the stoichiometric ratio (G/N= 1.5), both catalysts become dense in structure and contain less pores.